Penggerusan di Hilir Bendung dengan Mercy Type Vlugter - Maria Christine Sutandi; Kanjalia Tjandrapuspa; Ginardy Husada (Universitas Kristen Maranatha, 2016)
Indonesia is a developing tropical country. With abundant natural resources,especially water resources, as well as the conditions of agrarian society so that theagricultural sector has great potential and should be developed in Indonesia.To support this, we need a network of irrigation to irrigate the irrigation networkof the source is a river located upstream of the dam that required manufacture of theriver water level can be elevated, with the aim to reach a wider area of rice fields. Thestability of the weir is affected by scour downstream of the weir, so there should beresearch scouring downstream of the weir, in this study we used 2 type weir with 2 radiusSummit of Vlugter and the body of dam with slope 1: 1 and 3.5: 4. Having conductedresearch with a variety of discharge through, showed that scour downstream weirsmallest body caused by tilting weir 3.5: 4 but it also is the benefit of this study as amodel to be followed up with a prototype.